Pengaruh jenis media tanam dan aplikasi pupuk hayati mikoriza terhadap pertumbuhan, pembungaan dan infeksi mikoriza pada tanaman anggrek Dendrobium sp. - Herliana, Okti; Rokhminarsi, E; Mardini, S; Jannah, M (Kultivasi, 2018)
The research aimed to find out 1) the best growing media for growth and flowering of Dendrobium orchid, 2) the best dosage of mycorrhizal biofertilizer for growth and flowering of Dendrobium orchid, 3) the best combination type of growing media and mycorrhizal biofertilizer for growth and flowering of Dendrobium orchid. The research was conducted at Screen house of Datar Village, Sumbang Subdistrict, Banyumas Regency from May 2017 to November 2017. The research design was using Randomized Block Design (RBD) method with 2 factors and 3 replicates:(1) Growing media with 3 treatment types; wood charcoal, fern (Cyathea contaminans), root of the birdâs net fern (Asplenium nidus), and (2) dosage of mycorrhizal biofertilizer with 3 levels; without mycorrhizal, 10g /plant (20 spores), 20g /plant (40 spores). Data were analyzed by analysis of variance followed by Duncanâs Multiple Range Test (DMRT) at 5% level. The observed variables were the increase of plant height, number of leaves, the increase of leaf area, number of buds, number of roots, number of root length, the appearing of first primordia flower, the first flower blossom, number of flower per stalk, number of flower stalk per plant, length of flower stalk, and percent of mycorrhizal infections. The result of the research showed that root of the birdâs net fern is the best of growing media for variables of the number of leaves and the number of buds for each 5,63 leaves and 1,37buds, as well as the percentage of mycorrhizal infections by 54,44%. Result also showed that the best dosage of mycorrhizal biofertilizer is 10 g/plant for variables of the number of root and the percentage of mycorrhizal infections for each 20,78 roots and 64,44%. The highest number of flowers per stalk was obtained on the combination of growing media using fern (Cyathea contaminans) without mycorrhizal biofertilizer by 8 flowers.Anggrek merupakan tanaman hias yang potensial untuk dibudidayakan, karena mem-punyai nilai ekonomis tinggi. Penelitian ini bertujuan untuk mengetahui jenis media tanam dan dosis mikoria terbaik pada pertumbuhan dan pembungaan anggrek dendrobium serta mem-pelajari interaksi antara pemberian jenis media tanam dan dosis pupuk hayati mikoriza terhadap pertumbuhan, pembungaan anggrek Dendrobium sp. dan infeksi mikoriza. Penelitian dilaksanakan di Screen house Desa Datar, Kecamatan Sumbang, Kabupaten Banyumas mulai Mei hingga November 2017. Rancangan penelitian meng-gunakan rancangan acak kelompok pola faktorial dengan 2 faktor dan 3 ulangan, yaitu (1) media tanam dengan 3 jenis media; arang kayu, pakis (Cyathea contaminans), akar kadaka (Asplenium nidus), dan (2) dosis pupuk hayati mikoriza dengan 3 taraf; tanpa mikoriza, 10 g tanaman-1 (20 spora), 20 g tanaman-1 (40 spora) Hasil penelitian menunjukkan media akar kadaka merupakan media terbaik untuk variabel pertambahan jumlah daun dan jumlah tunas anggrek Dendrobium masing-masing yaitu sebanyak 5,63 helai dan 1,37 tunas, serta persen infeksi mikoriza sebesar 54,44%. Pupuk hayati mikoriza 10 g/tanaman merupakan dosis terbaik untuk variabel pertambahan jumlah akar dan persen infeksi mikoriza anggrek Dendrobium masing-masing sebanyak 20,78 akar dan 64,44%. Jumlah bunga per tangkai tertinggi diperoleh pada kombinasi jenis media tanam pakis dengan tanpa pupuk hayati mikoriza sebanyak 8 kuntum.Â Kata Kunci : Dendrobium sp., media tanam, pupuk hayati mikoriza, pertumbuhan dan pembungaa